Clinical Epidemiology Features and Risk Factors for Acute Diarrhea Caused by Rotavirus A in Vietnamese Children - Van Chuc, Dang; Linh, Dang Phuong; Linh, Dang Viet; Van Linh, Pham (International journal of pediatrics, 2023)
Introduction. Acute diarrhea caused by group A rotavirus (RVA) is a leading cause of morbidity and mortality globally in children less than 5 years old. Acute diarrhea caused by RVA is often manifested by loose/watery stool leading to different degrees of dehydration. The detection of risk factors, diagnosis, and prompt treatment of acute diarrhea caused by RVA is critical. We aimed to describe clinical epidemiological features of acute diarrhea caused by RVA and its associated risk factors. Subjects and Method. We conducted a cross-sectional study that included 321 children under 5 years old with acute diarrhea at Haiphong Children’s Hospital, Vietnam, from 1 August 2019 to 31 July 2020. Results. Among the 321 children included in our analysis, 221 (68.8%) children were positive for RVA. Males represented 61.1% of cases, 41.2% of children were in the 12-<24-month age group, and the majority of cases were among children in suburban areas (71.5%). Clinical manifestations included loose and watery stool (100%), vomiting-fever-loose/watery stool (57.9%), vomiting-loose/watery stool (83.2%), fever-loose/watery stool (58.8%), dehydration (30%), hyponatremia (22.1%), hypernatremia (1.4%), and hypokalemia (15%). Risk factors for acute diarrhea caused by RVA included history of diarrhea, not exclusive breastfeeding in the first 6 months, living area, maternal education, and income. Conclusions. Acute diarrhea due to RVA was very prevalent in children under 5 years old. Clinical manifestations included a high prevalence of loose/watery stools/day and dehydration with electrolyte disorder. Mothers should exclusively breastfeed their children for the first 6 months to avoid the risk of acute diarrhea caused by RVA.